An Introduction to Surface Alloying of Metals - Hosmani, Santosh S.; Kuppusami, P.; Goyal, Rajendra Kumar (Manufacturing and Surface Engineering, 2014)
An Introduction to Surface Alloying of Metals aims to serve as a primer to the basic aspects of surface alloying of metals. The book serves to elucidate fundamentals of surface modification and their engineering applications. The book starts with basics of surface alloying and goes on to cover key surface alloying methods, such as carburizing, nitriding, chromizing, duplex treatment, and the characterization of surface layers. The book will prove useful to students at both the undergraduate and graduate levels, as also to researchers and practitioners looking for a quick introduction to surface alloying.